FENOMENA TRADISI ZIARAH MAKAM K.H.R BAGUS KHASANTUKA DI DUSUN SENUKO SIDOAGUNG GODEAN SLEMAN - Norseta, Pandiga Aji (Universitas PGRI Yogyakarta, 2020)
This study aims to see the phenomena of the tradition of pilgrimage to the grave of K.H.R. Bagus Khasantuka in Dusun Senuko, Sidoagung, Godean, Sleman. The method used in this research is qualitative research methods. This study has two types of data and data sources, namely primary data and secondary data. Data collection techniques in this study were carried out by direct field observation, interviews, and documentation. The data analysis techniques used were data reduction, data presentation, and data collection. The data validity checking technique used was the source triangulation technique and the technique triangulation. The results of this study indicate the phenomenon of the pilgrimage tradition at K.H.R. Bagus Khasantuka’s grave intending to pray for and interpret the values of life. Pilgrims who visit the grave of waliyullah K.H.R. Bagus Khasantuka can trace the struggle of previous scholars in Islam. The existence of Sendang Bagusan as a legacy of K.H.R. Bagus Khasantuka is still used by the Javanese mystical adherents for the kungkum ritual to achieve certain goals. The development of the Tomb of K.H.R. Bagus Khasantuka also had a positive impact on the construction of hamlet roads, gates, and youth organization activities in Senuko Village.